Angiopoietin-like protein 2 promotes chondrogenic differentiation during bone growth as a cartilage matrix factor. Issue 1 (January 2018) - Tanoue, H.; Morinaga, J.; Yoshizawa, T.; Yugami, M.; Itoh, H.; Nakamura, T.; Uehara, Y.; Masuda, T.; Odagiri, H.; Sugizaki, T.; Kadomatsu, T.; Miyata, K.; et al.
Summary: Objective: Chondrocyte differentiation is crucial for long bone growth. Many cartilage extracellular matrix (ECM) proteins reportedly contribute to chondrocyte differentiation, indicating that mechanisms underlying chondrocyte differentiation are likely more complex than previously appreciated. Angiopoietin-like protein 2 (ANGPTL2) is a secreted factor normally abundantly produced in mesenchymal lineage cells such as adipocytes and fibroblasts, but its loss contributes to the pathogenesis of lifestyle- or aging-related diseases. However, the function of ANGPTL2 in chondrocytes, which are also differentiated from mesenchymal stem cells, remains unclear. Here, we investigate whether ANGPTL2 is expressed in or functions in chondrocytes. Methods: First, we evaluated Angptl2 expression during chondrocyte differentiation using chondrogenic ATDC5 cells and wild-type epiphyseal cartilage of newborn mice. We next assessed ANGPTL2 function in chondrogenic differentiation and associated signaling using Angptl2 knockdown ATDC5 cells and Angptl2 knockout mice. Results: ANGPTL2 is expressed in chondrocytes, particularly those located in resting and proliferative zones, and accumulates in ECM surrounding chondrocytes. Interestingly, long bone growth was retarded in Angptl2 knockout mice from neonatal to adult stages via attenuation of chondrocyte differentiation. Both in vivo and in vitro experiments show that changes in ANGPTL2 expression can also alter p38 mitogen-activated protein kinase (MAPK) activity mediated by integrin α5β1. Conclusion: ANGPTL2 contributes to chondrocyte differentiation and subsequent endochondral ossification through α5β1 integrin and p38 MAPK signaling during bone growth. Our findings provide insight into molecular mechanisms governing communication between chondrocytes and surrounding ECM components in bone growth activities.